1978
DOI: 10.1111/j.1600-0447.1978.tb03576.x
|View full text |Cite
|
Sign up to set email alerts
|

Addition of L‐tryptophan to electroconvulsive treatment in endogenous depression

Abstract: The combination of electroconvulsive treatment (ECT) and i.v. L-tryptophan (T) was compared with ECT and saline in double-blind study comprising 20 patients with endogenous depression. No significant difference was found with regard to the number of ECT given nor in the rate of reduction of depressive symptoms. Except for a slight decrease of plasma total tryptophan in the palcepo group, no difference were found in plasma total and free tryptophan nor in the concentration of total tryptophan in the cerebrospin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

1980
1980
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 21 publications
3
18
0
Order By: Relevance
“…Previous research demonstrated no alteration in TRP concentrations after a single or a course of repetitive ECT (Kirkegaard et al, 1978;Mokhtar et al, 1997;Whalley et al, 1980), whereas Palmio et al found an increase in TRP concentrations 2-24 h after a single ECT session (Palmio et al, 2005). Another study demonstrated lower TRP concentration and TRP availability after a course of repetitive ECT particularly in ECT responders (Hoekstra et al, 2001).…”
Section: Discussionmentioning
confidence: 89%
“…Previous research demonstrated no alteration in TRP concentrations after a single or a course of repetitive ECT (Kirkegaard et al, 1978;Mokhtar et al, 1997;Whalley et al, 1980), whereas Palmio et al found an increase in TRP concentrations 2-24 h after a single ECT session (Palmio et al, 2005). Another study demonstrated lower TRP concentration and TRP availability after a course of repetitive ECT particularly in ECT responders (Hoekstra et al, 2001).…”
Section: Discussionmentioning
confidence: 89%
“…54,55 None of 13 trials examining the efficacy of adjunctive or continuation pharmacotherapy adequately described the method of randomisation. Seven of these trials were double blind, [59][60][61]63,[66][67][68] four were single blind 57,58,62,64 and in two it was not clear whether the clinician or the patient was blind to treatment allocation. 56,65 One RCT examining the impact of the educational video on patient knowledge 69 used concealed randomisation, but was not blind and only measured knowledge at follow-up using an instrument with no evidence to support its psychometric properties.…”
Section: Quality Of Rcts Identified By the Nice Reviewersmentioning
confidence: 99%
“…Two trials compared unilateral ECT combined with L-tryptophan versus unilateral ECT and placebo. 59,60 Three trials compared ECT combined with imipramine versus ECT combined with placebo. 61,62,65 In one study the dosage of imipramine ranged from 25 to 50 mg, 61 in another the dosage was 25 mg three times daily 62 and in the third it ranged from 150 to 220 mg. 65 Imlah and colleagues 62 also had an arm in the trial where ECT was combined with phenelzine (15 mg three times daily).…”
Section: Ect Versus Rtmsmentioning
confidence: 99%
See 2 more Smart Citations